2015
DOI: 10.1371/journal.pone.0142067
|View full text |Cite
|
Sign up to set email alerts
|

Tackling Glaucoma from within the Brain: An Unfortunate Interplay of BDNF and TrkB

Abstract: According to the neurotrophin deprivation hypothesis, diminished retrograde delivery of neurotrophic support during an early stage of glaucoma pathogenesis is one of the main triggers that induce retinal ganglion cell (RGC) degeneration. Therefore, interfering with neurotrophic signaling seems an attractive strategy to achieve neuroprotection. Indeed, exogenous neurotrophin administration to the eye has been shown to reduce loss of RGCs in animal models of glaucoma; however, the neuroprotective effect was most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 69 publications
4
45
0
1
Order By: Relevance
“…Upon ONC, the number of brain-specific homeobox/POU domain protein 3A (Brn3a) + RGCs both in vehicle-and inhibitor-treated mice decreased progressively over time post-lesion, with a Brn3a + RGC survival rate in vehicle mice of approximately 62% at four days post injury (dpi), which is similar to previous reported studies [24,25,26]. However, MMP-12 inhibitor-treated mice showed a Brn3a + RGC survival of 74% at the same time post ONC (Figure 6A–C), clearly indicating that the number of Brn3a + RGCs was significantly higher in the MMP-12 inhibitor treated group compared to the vehicle control group, at 4 dpi (2.535 ± 35 vs. 2.149 ± 61; p < 0.001) (Figure 6C).…”
Section: Resultssupporting
confidence: 90%
“…Upon ONC, the number of brain-specific homeobox/POU domain protein 3A (Brn3a) + RGCs both in vehicle-and inhibitor-treated mice decreased progressively over time post-lesion, with a Brn3a + RGC survival rate in vehicle mice of approximately 62% at four days post injury (dpi), which is similar to previous reported studies [24,25,26]. However, MMP-12 inhibitor-treated mice showed a Brn3a + RGC survival of 74% at the same time post ONC (Figure 6A–C), clearly indicating that the number of Brn3a + RGCs was significantly higher in the MMP-12 inhibitor treated group compared to the vehicle control group, at 4 dpi (2.535 ± 35 vs. 2.149 ± 61; p < 0.001) (Figure 6C).…”
Section: Resultssupporting
confidence: 90%
“…Upregulation of BDNF expression preserved RGC loss and retina function from ischaemia/reperfusion injury caused by acute IOP elevation model (Igarashi et al 2016), and the effect could be sustained for up to 70 weeks (Ren et al 2012). Brainderived neurotrophic factor (BDNF) was also effective in transiently slowing down axotomy-induced RGC loss Zhi et al 2005;Parrilla-Reverter et al 2009;Nakatani et al 2011;Galindo-Romero et al 2013;Dekeyster et al 2015; Junyi et al (Blanco et al 2008).…”
Section: Exercise and Bdnf Expressionmentioning
confidence: 99%
“…However, Dekeyster et al [37] found that viral-vector-mediated upregulation of BDNF in the superior colliculus alone was unable to elicit a significant neuroprotective activity in murine models of optic nerve crush or laser-induced ocular hypertension. The authors suggest their observations to be a result of viral-vector-induced neurotrophin desensitisation, resulting in a failure of BDNF expressed in the superior colliculus to reach the retina via retrograde transport in both healthy mice and injury models.…”
Section: Techniques For Monitoring Retinal Ganglion Cell Healthmentioning
confidence: 99%